FACTORS AFFECTING MILLENNIAL GENERATION VOTING DECISION IN THE 2019 GENERAL ELECTION IN SURABAYA - Citra Oktavia Mochtar (Universitas Muhammadiyah Jember, 2020)
An election in a democratic country has become routine in determining the regeneration of leadership. Political participation, especially voting in elections, is the key to democratic governance. Millennial Generation or Millennials have great potential for political power because of their large numbers. Their voices cannot be taken lightly. Instead, Millennials can make a significant vote contribution for the presidential candidates. The formulation of the problems discussed in this study is about how leadership, emotional relations, mass media, political issues, and voters' attitudes affect the decision to elect Presidential candidates and Legislative candidates by millennial generations. This study was a quantitative study in which the data were collected by distributing questionnaires to millennials who lived in Surabaya City. The obtained data were then analyzed using Partial Least Square (PLS) analysis method. The findings showed that leadership, emotional connection, mass media, and voter attitudes had a positive significant effect on choosing candidates by the millennial generation. Meanwhile, political issues did not significantly influence their decision in choosing candidates in the 2019 general election in Surabaya.